MONEY POLITIC SEBAGAI REPRESENTASI BUDAYA PATRON-CLIENT DALAM PEMILU: PERSPEKTIF SOSIOLOGI POLITIK - Asra, Saiful; Mauliansyah, Fiandy (Jurnal Society : Pengamat Perubahan Sosial, 2024)
This study examines money politics as a representation of patron-client culture in elections, focusing on its implications for democratic integrity in Indonesia and other developing countries. The primary issue addressed is how money politics, through financial incentives, reinforces dependency between political elites and voters, undermining fair electoral processes. The research aims to analyze the socio-political dynamics of money politics and its impact on democratic governance. Using a qualitative approach, the study relies on literature review and secondary data analysis, including academic journals, election reports, and media articles. The findings reveal that money politics perpetuates systemic corruption, exacerbates social and political inequalities, and weakens public trust in democratic institutions. The study concludes that addressing money politics requires comprehensive reforms, including stricter campaign finance regulations, enhanced political literacy, and stronger democratic institutions. This research highlights the importance of understanding money politics within the framework of patron-client relationships to develop effective strategies for promoting fair and inclusive democratic practices.Keywords: Money Politics; Patron-Client; Election; Political-Sociology